New Cancer Paradigm and New Treatment: The Example of METABLOC. (10th September 2013) - Schwartz, Laurent; Summa, Mireille; Steyaert, Jean Marc; Guais-Vergne, Adeline; Baronzio, Gian Franco
Abstract : Hyperthermia has long been known to interfere with the tumor metabolism. The goal of this paper is to review the potential of metabolic therapy and to suggest that its combination with hyperthermia may be of interest.